REVITALISASI ISLAM KULTURAL - Jamil, M. Mukhsin (WALISONGO, 2013)
AbstractThis research aim to explore one of Islamic movements in Indonesia after reformationof 1998. By using qualitative method, it is clear that the demarcation betweeen Islamictradisionalism and Islamic modernism fluided culturally. Although at the same timepolarization both become more political, which is made Indonesian Islamicmainstream loosed elan vital as sosial and cultural movement. There is thecontradictory trends in the dynamic of Islamic thought and movement introduced byIslamc minority groups. In one side the trends are multiculturalism, anti coruptionmovement and appreciation to the local cultures which is ignorenced before by Islamicmovement in Indonesia. In other side, political oriented in many Islamic movement isstronger. The dominant of traditional constructions of Islamic polical thought of sunni(fiqh al-siyasah) influenced to the Islamic movement to state orientation at same timeignored the society with their problem and cultural expression. The cultural Islamproposed new understanding to Islamic traditions with hermeneutic and remove thelocus of movement forum political Islam to civil Islam.***Penelitian ini bertujuan untuk menjelajahi salah satu gerakan Islam di Indonesiasetelah reformasi 1998. Dengan menggunakan metode kualitatif, akan menjadi jelasdemarkasi antara Islam tradisional dan Islam modernis secara kultural. Meskipolarisasi kedua kelompok keagamaan itu kerap bernuansa lebih politis, sehinggamenghilangkan elan vital Islam Indonesia sebagai gerakan sosial dan budaya. Tetapiada tren kontradiktif dalam dinamika pemikiran dan gerakan Islam yang dilakukanoleh kelompok minoritas Islam. Di satu sisi trennya adalah multikulturalisme,gerakan anti korupsi, dan apresiasi terhadap budaya lokal yang telah dikembangkanoleh gerakan Islam sebelumnya. Di sisi lain, orientasi politik kelompok keagamaanjuga semakin meningkat. Dominasi pemikiran politik tradisional Sunni turutmempengaruhi pola gerakan Islam kepada negara dan pada saat yang samamengabaikan masyarakat dengan problem kebudayaan mereka. Islam kulturalmencoba untuk meniupkan pemahaman baru dalam tradisi Islam denganhermeneutika dan menggeser arah gerakan Islam politik kepada Islam sipil.Keywords: Islam kultural, civil Islam, Islam politik